A single-cell transcriptome atlas of the maturing zebrafish telencephalon - Pandey, Shristi; Moyer, Anna J.; Thyme, Summer B. (Genome Research, 2023)
The zebrafish telencephalon is composed of highly specialized subregions that regulate complex behaviors such as learning, memory, and social interactions. The transcriptional signatures of the neuronal cell types in the telencephalon and the timeline of their emergence from larva to adult remain largely undescribed. Using an integrated analysis of single-cell transcriptomes of approximately 64,000 cells obtained from 6-day-postfertilization (dpf), 15-dpf, and adult telencephalon, we delineated nine main neuronal cell types in the pallium and eight in the subpallium and nominated novel marker genes. Comparing zebrafish and mouse neuronal cell types revealed both conserved and absent types and marker genes. Mapping of cell types onto a spatial larval reference atlas created a resource for anatomical and functional studies. Using this multiage approach, we discovered that although most neuronal subtypes are established early in the 6-dpf fish, some emerge or expand in number later in development. Analyzing the samples from each age separately revealed further complexity in the data, including several cell types that expand substantially in the adult forebrain and do not form clusters at the larval stages. Together, our work provides a comprehensive transcriptional analysis of the cell types in the zebrafish telencephalon and a resource for dissecting its development and function.
10.1101/gr.277278.122